The Effectivness Assessment Of Human Capital In Tourism Entities In Municipality Mielno (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of this paper is a comparative analysis of the human capital profitability in companies operating in tourism industry in the municipality Mielno. The ratio analysis used efficiency indicators of human capital such as: the profitability of the labor cost index HCR CFTE and PTFE. It was assumed that investigated companies support development of human capital, but the achieved profitability varies in both companies.
Keywords: profitability; human capital; investment